PENGARUH SENAM OTAK DALAM MENINGKATKAN FUNGSI KOGNITIF DAN KESIAGAAN MENGHADAPI GANGGUAN KONSENTRASI PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA SIDIKALANG - Berutu, Heriaty; Lingga, Rugun Togianur; Arianti, Wiwik Dwi (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
ABSTRACT Education for early childhood is an effort to provide and provide guidance to help the physical and spiritual growth and development of children from birth to 6 years of age so that they are ready to enter the next stage of education. The quality of a child's future development is largely determined by the stimulation they receive from an early age. Providing educational stimulation is very important, because 80% of brain growth develops at an early age. Brain exercises are used as a method to improve cognitive abilities or memory and concentration in children. This research aims to determine the effect of brain exercises in improving cognitive function and preparedness to deal with concentration disorders in students at Pembina Kindergarten, Dairi Regency. The study design in this research is quasi experimental with one group pre test and post test design. Determining the sample for this study used the G-Power application version 3.1.9.7 with T-test, one tail, effect size 0.85, alpha error 0.05, and power 0.80, so a minimum of 16 plus a possibility of error of 10% are needed, so the respondents needed in this study totaling 18 respondents. Brain exercise is carried out 3 (three) times a week for a week and evaluation is carried out on the seventh day. The results of this study used bivariate analysis, namely the Wilcoxon statistical test to identify cognitive function and preparedness for facing concentration problems before and after brain exercise. The results of this study show that there are differences in cognitive function and preparedness for concentration disorders between before and after brain exercise with a P value of 0.002 and a P value of 0.001. This shows that there is a statistically significant difference in cognitive function and preparedness for dealing with concentration problems before and after being given the intervention with a P value <0.05. Conclusion: Brain exercise training has an effect on cognitive function and preparedness for facing concentration problems in children 4-5 years old in Kindergarten Pembina, Dairi Regency.